Simultaneous laser beam melting of multimaterial polymer parts - Laumer, Tobias; Stichel, Thomas; Amend, Philipp; Schmidt, Michael (Journal of Laser Applications, 2015)
By simultaneous laser beam melting (SLBM), parts consisting of different polymer powders can be additively manufactured within one building process. Besides the advantages of conventional LBM, e.g., not needing additional tools and being able to realize parts with almost any geometry, different product requirements can be achieved within a single part. Product requirements may be different chemical resistances or haptic material properties. Therefore, SLBM enlarges the application field for additive manufacturing in general. In the process, two different materials are deposited on the building platform and preheated a few degrees below the melting temperature of the lower melting polymer by infrared emitters. Afterward, a CO2 laser (λ=10.6μm) provides the energy for the temperature difference between the preheating temperatures of both materials. Finally, a digital light processing chip is used to achieve simultaneous and flexible energy deposition for melting both preheated polymers. By illuminating the chip with a laser, parts of the beam can be flexibly guided onto the powder bed or into a beam trap. As laser, a single mode thulium laser (λ=1.94μm) is used. After melting the layer, a new layer is deposited and the process starts anew. In this paper, polypropylene and polyamide 12 are used as materials. After analyzing the material and melting behavior during the process by a high-resolution thermal imaging system, the parts are qualified regarding their material compatibility at the boundary zone and porosity by cross sections.
Created from Fastlane, Scopus look-up
Keywords: additive manufacturing; material qualification; multi-material parts; new processes